Psychological Effects on Children in Families Where Both Parents Are Sociologists: A Comprehensive Study - Anam Batool; Awais Ur Rahman; Sana Sher; Aisha Iqbal Khan; Rubia Batool; Arfa Akram (Dialogue Social Science Review (DSSR), 2025)
This research explores psychological effects on children whose parents are sociologists. It provides a comprehensive analysis of the professional background effect of two sociologist parents on the styles of parenting and how children grow up by using qualitative approaches. In-depth interviews were conducted on 50 participants, consisting of 25 sociologists with their respective children. The results show that sociologist parents are mostly authoritative due to the fact that it offers space for freedom, reflection, and sociality. Children with such personalities tend usually to display high self-esteem, extraordinary cognitive skills, and adequate knowledge of social circles. Some children suffer stress due to sky-high expectations. Such a study underlines the balance between intellectual stimulation on one hand and emotional support on the other. It throws light upon how professional careers, especially in the field of sociology, influence family life and the growth of a child. The findings from the present study will help improve the understanding of how parental occupations relate to psychological and social outcomes in children.